GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 634 species occurrences available in GBIF matching the query: TaxonKey: Panthera onca (Linnaeus, 1758) HasCoordinate: true HasGeospatialIssue: false. The dataset includes 634 records from 43 constituent datasets: 4 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 39 records from Paleobiology Database. 13 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 2 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 1 records from TTU Mammals Collection. 1 records from PSM Vertebrates Collection. 31 records from Field Museum of Natural History (Zoology) Mammal Collection. 3 records from NMNH occurrence DwC-A. 3 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 44 records from CNMA/Colección Nacional de mamíferos. 24 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 4 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 131 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 2 records from LSUMZ Mammals Collection. 5 records from LACM Vertebrate Collection. 1 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 7 records from UMMZ Mammal Collection. 1 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 22 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 28 records from iNaturalist research-grade observations. 1 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 1 records from Macaulay Library Audio and Video Collection. 2 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 18 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 1 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 1 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 19 records from Mammals housed at MHNG, Geneva. 68 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 3 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 4 records from DMNS Mammal Collection (Arctos). 3 records from naturgucker. 2 records from CAS Mammalogy (MAM). 3 records from Inventario de los mamíferos de las reservas de la biósfera Mapimí, La Michilía, El Cielo y Calakmul. 38 records from Computarización de la Colección Nacional de mamíferos del Instituto de Biología, UNAM. 28 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 13 records from Mammalogy Collection - Royal Ontario Museum. 29 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from South Australian Museum Australia provider for OZCAM. 2 records from MVZ Mammal Collection (Arctos). 8 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 4 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 17 records from KUBI Mammalogy Collection. 2 records from University of California Museum of Paleontology.
Keywords: GBIF; biodiversity; species occurrences